Australia : Benefiting from Economic Reforms. (International Monetary Fund, 1998)
Australia's recent economic performance has been impressive. It has experienced steady growth since the early 1990s and inflation has averaged just 2 percent over the same period. This strong showing marks a departure from the performance of the postwar years, when falling productivity and rising inflation caused Australia's per capita income to slip from one of the highest among OECD countries to merely average. This economic turnaround is explored in this book edited by Anoop Singh, Josh Felman, Ray Brooks, Tim Callen, and Christian Thimann of the Asia and Pacific Department.